Hubungan Kepatuhan Minum Obat Hipertensi dengan Kualitas Hidup Lasia di Wilayah Kerja Puskesmas Sei Langkai Kota Batam - Novrizal, Yogi; Alba, Afif D. (PPNI UNIMMAN, 2025)
Hypertension is a common health problem in the elderly that can affect quality of life. Hypertension in Batam city is a non-communicable disease that ranks 2 and with a percentage of 30.9%. The World Health Organization (WHO) said that there are 50 70% of hypertensive patients who do not comply with prescribed medications. Compliance with taking antihypertensive drugs is important to maintain blood pressure stability. Non-compliance in using antihypertensive drugs is one of the risk factors for increasing morbidity and uncontrolled hypertension events that can worsen the quality of life of hypertensive patients. This study aims to find out